2019
DOI: 10.4252/wjsc.v11.i9.693
|View full text |Cite
|
Sign up to set email alerts
|

Bioactive lipids in cancer stem cells

Abstract: Tumours are known to be a heterogeneous group of cells, which is why they are difficult to eradicate. One possible cause for this is the existence of slow-cycling cancer stem cells (CSCs) endowed with stem cell-like properties of self-renewal, which are responsible for resistance to chemotherapy and radiotherapy. In recent years, the role of lipid metabolism has garnered increasing attention in cancer. Specifically, the key roles of enzymes such as stearoyl-CoA desaturase-1 and 3-hydroxy-3-methyl-glutaryl-coen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
19
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
4
4
2

Relationship

1
9

Authors

Journals

citations
Cited by 29 publications
(19 citation statements)
references
References 122 publications
(129 reference statements)
0
19
0
Order By: Relevance
“…Furthermore, many studies have shown that increased lipid synthesis helps to maintain CSCs. It is an important source of metabolic intermediates and energy needed for cell growth and stemness-related pathways 47,[49][50][51][52][53] .…”
Section: Sas Tumour Spheres Demonstrated Enhanced Cisplatin Resistancementioning
confidence: 99%
“…Furthermore, many studies have shown that increased lipid synthesis helps to maintain CSCs. It is an important source of metabolic intermediates and energy needed for cell growth and stemness-related pathways 47,[49][50][51][52][53] .…”
Section: Sas Tumour Spheres Demonstrated Enhanced Cisplatin Resistancementioning
confidence: 99%
“…Several lipogenic genes are reprogrammed in CSCs and are critical for CSCs maintenance. Although these mechanisms require further investigation, FAS was found to be involved in CSCs survival in several cancer cell types such as glioma, pancreatic tumors or breast cancer [ 86 ]. Knockdown of ACLY inhibits epithelial–mesenchymal transition, a phenomenon related to cancer stemness [ 87 ].…”
Section: Changes In Lipid Metabolism Contribute To Anticancer Drugmentioning
confidence: 99%
“…DGAT2 catalyzes the nal step in synthesis triglyceride, which is a major component of LDs [36], and genetic deletion of DGAT2 was lethal with knockout mice presenting severe and systemic reductions in triglyceride [37]. SCD is a principal enzyme responsible for fatty acid desaturation, which is critical for growth, survival and tumorigenesis [25,38]. ENPP2, also known as Autotaxin (ATX), is always overexpressed in many malignancies [39], including MCL [40].…”
Section: Discussionmentioning
confidence: 99%